Carbon - carbon composites: Effect of graphene size upon the nano-micro - structure and material properties. (July 2021) - Singh, Madhu; Vander Wal, Randy
Abstract: This work aims to address the effect of filler size in the formation of Carbon-carbon (C-C) composites using two carbon-based matrices that show opposite behaviors when subjected to graphitization temperatures. Matrix precursors are anthracene (forms a graphitizable carbon) and Novolac (forms a non-graphitizable carbon). These materials are mixed with pre-synthesized carbon-based fillers. The fillers are different sizes of few layer graphene sheets - (a) small graphene (average X-Y = 500 nm) (b) medium graphene (average X-Y = 1.5 µm) (c) large graphene (average X-Y = 4 µm). The composite mixture is then subjected to carbonization and graphitization. By size of graphene filler, opposite trends are demonstrated for the two matrix precursors. Anthracene-based composites become non-graphitizing while novalac-based composites become graphitizing. The six C-C composites so formed are characterized at different length scales – nano, micro and macro. Such characterization helps analyze the variation in their evolving structure with graphene filler size, thus helping correlate C-C structure to observed bulk properties. Graphical abstract: Image, graphical abstract